2014
DOI: 10.1016/j.jcrysgro.2013.12.064
|View full text |Cite
|
Sign up to set email alerts
|

Modeling the nucleation statistics in vapor–liquid–solid nanowires

Abstract: The full-text may be used and/or reproduced, and given to third parties in any format or medium, without prior permission or charge, for personal research or study, educational, or not-for-prot purposes provided that:• a full bibliographic reference is made to the original source • a link is made to the metadata record in DRO • the full-text is not changed in any way The full-text must not be sold in any format or medium without the formal permission of the copyright holders.Please consult the full DRO policy … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
9
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 29 publications
(71 reference statements)
0
9
0
Order By: Relevance
“…This discussion is limited to a simplified case of zero As evaporation from the catalyst. However, Sibirev and coauthors showed that a similar convergence of the LDs to a time-independent shape is observed when the evaporation is included. We will therefore proceed with the model without evaporation for further estimates, which is acceptable because the contribution into the saturated variance due to antibunching appears negligible anyway.…”
mentioning
confidence: 80%
“…This discussion is limited to a simplified case of zero As evaporation from the catalyst. However, Sibirev and coauthors showed that a similar convergence of the LDs to a time-independent shape is observed when the evaporation is included. We will therefore proceed with the model without evaporation for further estimates, which is acceptable because the contribution into the saturated variance due to antibunching appears negligible anyway.…”
mentioning
confidence: 80%
“…In III-V NWs, forming even a single ML may then significantly deplete the droplet in group V atoms. We demonstrated experimentally and theoretically that this has a strong impact on the statistics of nucleation [2,20,21]: depletion makes a new nucleation less likely after a first one than before, so that the nucleation events are anti-correlated in time. This nucleation antibunching (which may also yield NW ensembles with very uniform lengths [22][23][24]) consists in the depletion induced by the fast growth of a ML affecting the formation of subsequent MLs.…”
Section: Introductionmentioning
confidence: 97%
“…In the case of semiconductor nanowires (NWs) fabricated by the metalcatalyzed vapor-liquid-solid (VLS) method 10 , the ZNR is thought to determine the probability of 2D nucleation from a supersaturated liquid alloy of a metal catalyst with the growth constituencies 2 . In this way, the ZNR controls the vertical growth rate of NWs 2,11-13 , nucleation statistics in VLS NWs [14][15][16][17] , morphology of the growth interface 18,19 and even the preferred crystal structure of Au-catalyzed III-V NWs which can be either cubic zincblende (ZB) or hexagonal wurtzite (WZ) [20][21][22][23][24][25][26][27][28][29][30][31][32][33][34] . Since most NWs grow in the so-called mononuclear mode with only one island emerging in each NW monolayer (ML) 2 , we need to consider the chain of individual nucleation events.…”
Section: Introductionmentioning
confidence: 99%
“…This ZNR is widely used in modeling the size distribution of different “clusters” such as droplets and three-dimensional (3D) or two-dimensional (2D) surface islands. In the case of semiconductor nanowires (NWs) fabricated by the metal-catalyzed vapor–liquid–solid (VLS) method, the ZNR is thought to determine the probability of 2D nucleation from a supersaturated liquid alloy of a metal catalyst with the growth constituencies . In this way, the ZNR controls the vertical growth rate of NWs, , nucleation statistics in VLS NWs, morphology of the growth interface, , and even the preferred crystal structure of Au-catalyzed III–V NWs which can be either cubic zincblende (ZB) or hexagonal wurtzite (WZ). Since most NWs grow in the so-called mononuclear mode with only one island emerging in each NW monolayer (ML), we need to consider the chain of individual nucleation events. This simplifies modeling due to the absence of any collective effects or ensembles of nuclei.…”
Section: Introductionmentioning
confidence: 99%